2016
DOI: 10.3126/jmmihs.v2i0.15793
|View full text |Cite
|
Sign up to set email alerts
|

Needs assessment of mental health training for Auxiliary Nurse Midwives: a cross-sectional survey

Abstract: Mental health in pregnant women and new mothers is increasing recognised on the global health agenda. In Nepal mental health is generally a difficult to topic to discuss. THET, a London-based organisation, funded Bournemouth University, and Liverpool John Moores University in the UK and Tribhuvan University in Nepal to train community-based maternity workers on issues around mental health.This paper reports on a quantitative survey with nearly all Auxiliary Nurse Midwives in Nawalparasi (southern part of Nepal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Health workers reported that mental disorders were life-long conditions that had no effective treatment. The general public stated that mental disorders could not be cured by Western biomedicine but only through traditional healing (Kisa et al ., 2016; Simkhada et al ., 2016; Koirala et al ., 2019; Lamichhane, 2019; Kaiser et al ., 2020). This was also reflected in conceptions about the use of psychotropic medications for mental health conditions; most people described that once a person starts taking medications, she/he must take it for life (Upadhaya et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Health workers reported that mental disorders were life-long conditions that had no effective treatment. The general public stated that mental disorders could not be cured by Western biomedicine but only through traditional healing (Kisa et al ., 2016; Simkhada et al ., 2016; Koirala et al ., 2019; Lamichhane, 2019; Kaiser et al ., 2020). This was also reflected in conceptions about the use of psychotropic medications for mental health conditions; most people described that once a person starts taking medications, she/he must take it for life (Upadhaya et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, we need to train existing community health workers, primary care providers on the range of issues around mental health and mental illness. For example, a recent project used UK healthcare workers that volunteered to train ANMs (auxiliary nurse midwives) in Nawalparasi (southern Nepal) on a range of mental health issues [48,49]. Theory of change was used to integrate mental health into primary health care services by training healthcare workers, finding volunteers for community champion on mental health within the community in Nigeria [50].…”
Section: Strategies To Achieving Cultural and Attitudinal Changes Towmentioning
confidence: 99%
“…The project also suggested the need for perinatal mental health training to improve their knowledge and practice. [ 13 ] In addition, a recent systematic review recommended that it is crucial to incorporate mental health training in midwifery curriculum to empower midwives to identify and manage women with maternal mental health issues. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%